An Experimental Study For Emission Of Four Stroke Carbureted And Fuel Injection Motorcycle Engine - Katijan, Adnan; Abdul Latif, Mohd Faruq; Zahmani, Qamar Fairuz; Zaman, Shahid; Abdul Kadir, Khairuldean; Veza, Ibham (Penerbit Akademia Baru, 2019)
Each manuscript should contain an abstract of about 200 words and should be typed using Palatino Linotype, Font size 10. The manuscript has to be camera ready. Antipollution laws in many countries impose a limit on the volume of poisonous gases which may be emitted from a vehicle’s exhaust. The aim of this study is to compare the emission characteristic of a carbureted and fuel injection system of a four-stroke motorcycle engine. For this objective, a carbureted engine of Honda Wave 125 cc was converted into a fuel injection system. Emissions of CO, CO2 and hydrocarbon (HC) were measured in the lab. The test was conducted at three different speeds: 2000, 4000 and 6000 RPM; and at two loads: 5Nm and 10Nm. Upon conversion of the motorcycle engine, the results show improvement in term of reduction of emissions of all three gasses. Emission at a 5 Nm load improved by 62.6%, 29.75% and 11.33% for CO, HC and CO2 respectively. The results also showed a similar trend at a 10 Nm load, where the emissions improved to 75.86%, 30.1% and 47.71% for CO, CO2 and HC respectively. The results show that fuel injection is evidently a better system as it delivers lower emissions